Experiencing food, designing dialogues : proceedings of the 2nd International Conference on Food Design and Food Studies (EFOOD 2019), 28-30 November, 2019, Lisbon, Portugal /: proceedings of the 2nd International Conference on Food Design and Food Studies (EFOOD 2019), 28-30 November, 2019, Lisbon, Portugal. (2020) - Unknown
No abstract available